ENTREPRENEURIAL INTENTION AMONG COLLEGE STUDENTS WITH SPECIAL REFERENCE TO TIRUCHENDUR TALUK (International Journal of Food and Nutritional Sciences, 2022)
Making a living or earning money via the production, acquisition, and sale of goods and services is known as business. Entrepreneurial Intentions are seen as a personal perspective that motivates people to start new businesses. Higher levels of entrepreneurial intent greatly increase one's chances of becoming an entrepreneur. This essay made an effort to examine students' attitudes about entrepreneurship and the elements that affect it. Innovation and uniqueness of ideas are seen as essential components for a successful business. Taking this into account, the study was carried out among undergraduate students from Tiruchendur arts and science colleges. Students' responses to a self-administered survey with a structured questionnaire are used to gather data. It also analyses various impediments that students think to exist when choosing entrepreneurship as a career.